Alcohol consumption in women and the elderly : When does it induce heart failure? - Pankuweit, S (Herz, 2016)
The association between alcohol consumption and the etiology and prognosis of cardiovascular diseases has been the focus of attention and also the subject of controversial discussions for many years. This is particularly true for heart failure, which can be induced by coronary artery disease (CAD), arterial hypertension, atrial and ventricular arrhythmias and cardiomyopathies. Acute effects of high doses of alcohol can lead to impairment of the cardiac contraction strength with rhythm disturbances (holiday heart syndrome), transient ischemic attacks and in rare cases to sudden cardiac death. The chronic effects of high alcohol consumption include in particular, ventricular dysfunction, chronic rhythm disturbances, alcoholic cardiomyopathy and CAD. In contrast, light to moderate consumption of alcohol is associated with a reduced risk of CAD and ischemic stroke; however, even moderate alcohol drinking is associated with a greater risk for atrial fibrillation. The unfavorable effects of alcohol occur at much lower levels of acute or chronic consumption in women than in men. In the elderly just as in young people, a moderate alcohol consumption is associated with a lower risk of heart failure.